2022
DOI: 10.1101/2022.11.21.517388
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteome mapping of the human pancreatic islet microenvironment reveals endocrine-exocrine signaling sphere of influence

Abstract: The need for a clinically accessible method with the ability to match protein activity within heterogeneous tissues is currently unmet by existing technologies. Our proteomics sample preparation platform, named microPOTS (Microdroplet Processing in One pot for Trace Samples), can be used to measure relative protein abundance in micron-scale samples alongside the spatial location of each measurement, thereby tying biologically interesting proteins and pathways to distinct regions. However, given the smaller sam… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Using LCM, it is possible to cut out a single cell, 26,73 or to cut out larger pixels of an arbitrary shape and size. 91,97,98 Larger pixels will contain more peptides and increase MS signal. This is important as the number of peptide identifications in SCP is heavily determined by the amount of peptide material.…”
Section: Resolutionmentioning
confidence: 99%
“…Using LCM, it is possible to cut out a single cell, 26,73 or to cut out larger pixels of an arbitrary shape and size. 91,97,98 Larger pixels will contain more peptides and increase MS signal. This is important as the number of peptide identifications in SCP is heavily determined by the amount of peptide material.…”
Section: Resolutionmentioning
confidence: 99%
“…Nanodroplet processing in onepot for trace samples (nanoPOTS), and its companion microPOTS, have enabled routine single cell proteomics and BUP processing of dissected tissues. [28][29][30] In a previous study, we demonstrated the coupling of nanoPOTS sample preparation with TDP enabling the identification of over 150 proteoforms along with various PTMs from roughly 70 cultured HeLa cells. 31 This technology was further extended to spatial TDP by integrating nanoPOTS with LCM to identify an average of 509 proteoforms per 100,000 µm 2 dissection in brain tissue.…”
Section: Introductionmentioning
confidence: 99%
“…This special issue of Molecular and Cellular Proteomics presents a wide range of primary research, reviews, and perspectives pertaining to clinical proteomics. The expanding scope of proteomics applications is reflected in the spectrum of disease foci represented, including neurodegenerative diseases ( 1 , 2 , 3 , 4 ), infectious disease ( 5 , 6 ), endocrinology ( 7 , 8 ), cardiovascular disease ( 9 ), inflammatory disease ( 10 ), kidney disease ( 11 ), and cancer ( 12 , 13 , 14 , 15 ), as well as in the burgeoning areas of health monitoring and exercise ( 16 , 17 ).…”
mentioning
confidence: 99%
“…Complex cross-sectional, longitudinal and multi-omic analyses are facilitated by accelerating computer speeds, storage capabilities, and the promulgation of computational methods focused on proteomics ( 17 , 18 ). Improved sample-handling methods and instrument sensitivity have contributed to the expansion of spatially-resolved proteomics applications ( 8 ). Prior technological limitations that have prevented large numbers of patient samples from being analyzed have been greatly reduced owing to highly multiplexed strategies ( 3 , 4 , 6 , 8 ), far more sensitive MS systems, and new scanning methods such as data independent acquisition.…”
mentioning
confidence: 99%
See 1 more Smart Citation